Interesterified palm oil increases intestinal permeability, promotes bacterial translocation, alters inflammatory parameters and tight-junction protein genic expression in Swiss mice. (January 2022) - Menta, Penélope Lacrísio Reis; Andrade, Maria Emília Rabelo; de Castro, Lívia Furquim; Trindade, Luísa Martins; Dias, Melissa Tainan Silva; Miyamoto, Josiane Érica; dos Santos, Raisa Magno; Cassali, Geovanni Dantas; Leal, Raquel Franco; Ribeiro, Ana Paula Badan; Grimaldi, Renato; Ignacio-Souza, Letícia Martins; et al.
Graphical abstract: Highlights: Interesterified fat (IF) and High-fat (HF) diets cause damage to the intestinal mucosa and increase intestinal permeability. IF in normolipidic diet increases the bacterial translocation to the blood, liver, and lungs, while in HF diet this seems to be restricted to mesenteric lymph nodes. IF and HF diets increase the number of inflammatory cells and oxidative stress in the intestinal mucosa. IF added to normolipidic and to HF diets alters tight-junction proteins expression and inflammatory cytokine secretion. IF in normolipidic diet can be as harmful as HF diet to intestinal epithelium. Abstract: High-fat diets seem to have a negative influence on the development of obesity and the processes associated with low-grade chronic systemic inflammation. In recent years, partial hydrogenated oil, rich in trans isomers, has been associated with deleterious health effects. It has been replaced by interesterified fat (IF). However, there is no evidence whether IF ingestion can exert adverse effects on the intestinal mucosa. Thus, this study aimed to evaluate the effect of IF on the intestinal mucosa of male Swiss mice fed a normal or high-fat diet, focusing on its effects on intestinal permeability and bacterial translocation and its possible damage to the intestinal epithelium. The animals were divided into 4 groups: Control (C) and Interesterified Control (IC) groups (10 En% lipids from unmodified fat or interesterified fat, respectively) and High Fat (HF) and Interesterified High Fat (IHF) groups (45 En% lipids from unmodified fat or interesterified fat, respectively). Compare to C, the IC, HF, and IHF groups presented flattened epithelium, a shorter villi length and a lower percentage of goblet cells, less mucin 2, an increased oxidative stress and more inflammatory cells, higher IL-1β, IL-17, and IL-23 levels. These groups also presented increased intestinal permeability and gene expression of the protein claudin 2, while JAM-A and claudin 1 gene expression was reduced. IC and IHF increased IL-6 levels while reducing occludin expression. In addition, the IC group also presented a mucosa with lesions of low intensity in the ileum, an increased mucin 5ac, TNF-α levels, and reduced occludin expression in the distal jejunum. Moreover, there was a significant increase in bacterial translocation in the IC group to blood, liver, and lungs, while HF and IHF groups presented bacterial translocation which was restricted to the mesenteric lymph nodes. In summary, our results supported the hypothesis that IF added to a normolipidic diet can be considered harmful or even worse when compared to a HF.